Candidate Soluble Immune Mediators in Young Women with High-Risk Human Papillomavirus Infection: High Expression of Chemokines Promoting Angiogenesis and Cell Proliferation. - Zanotta, Nunzia; Tornesello, Maria Lina; Annunziata, Clorinda; Stellato, Giovanni; Buonaguro, Franco Maria; Comar, Manola (PLoS One, 2016)
BACKGROUND: The causal interpretation of cervical immune response to Human Papillomavirus (HPV) infection is complex and poorly characterized mainly due to the delicate balance that exists between viral infection, increase of inflammatory cytokines and host risk factors. This study aims to explore the significance of cervical immune mediators associated to cell survival, angiogenesis and interaction with immune response, in predicting the risk to develop HPV-related intraepithelial lesions. METHODS: A panel of 48 cytokines and growth factors were explored in a selected cohort of 168 immunocompetent women including 88 diagnosed with low (LSIL) or high (HSIL) squamous intraepithelial lesions of the cervix and 80 with normal cervical cytology (NIL). HPV genotyping was performed by Linear Array HPV test and the soluble concentration of 48 immune molecules was analyzed using the Bio-Plex platform. RESULTS: The prevalence of single HR-HPV infection was 30% in NIL and 100% in LSIL and HSIL women. The expression of 13 cytokines, including interleukins IL-6, IL-3, IL-12p40, IL-12p70, IL-16, IL-18, LIF, of chemokines CCL7 (MCP-3), CXCL9 (MIG), CXCL12 (SDF-1α) and of the tropic factors VEGF, G-CSF, M-CSF were significantly associated with the presence of infection, with levels being higher in women with precancerous lesions compared to NIL HPV negative women. Only the growth factor GM-CSF was positively associated with the cytological abnormalities. CONCLUSIONS: The ability of HR-HPV to escape from innate immune recognition and to orchestrate the production of specific inflammatory and growth factors, involved in early inflammatory response and in the cell-proliferating phase of intraepithelial damage, was documented in women before the development of cervical lesions.
Keywords: Adult; Cell Survival; Cervix Uteri; Chemokines; Cohort Studies; Female; Humans; Neovascularization, Pathologic; Papillomaviridae; Papillomavirus Infections